Severe open bite with mandibular asymmetry treated using micro-implant anchorage - Liao Jing; He Shushu; Hu Zhiai; Zou Shujuan (Sciendo, 2017)
This case report describes the orthodontic treatment of a 20 year-old female who presented with a severe anterior open bite, increased lower facial height and mandibular asymmetry. The patient was diagnosed with a Class I skeletal pattern but a Class III dental relationship, an anterior and unilateral posterior open bite, a canted posterior occlusal plane, a clockwise rotation and vertical growth pattern of the mandible incorporating a chin deviation to the right.